POTENSI KELEMBAGAAN LOKALDALAM PENGELOLAAN DAERAH ALIRAN SUNGAI (Studi Kasus di Desa Cemplang - Messalina L Salampessy; Ina Lidiawati (Jurnal Hutan Tropis, 2017)
Watershed Management becomes an important aspect in supporting the conservation of the surrounding area. Upstream area functions as a water catchment area must be kept by maintaining the utilization of the area to avoid the carrying capacity beyond the environment. The role of people in the surrounding area becomes an important effort to maintain the continuity of the function of the Watershed. This study aims to analyze the potency of local institutional support in watershed management. The research method is a case study in which data are collected through in-depth interviews, focus group discussions and participant observation. The data analysis is conducted by using situation framework approach - structure - behavior - performance. The results show that the utilization of watershednaturalresource is considered as a free open source access where everyone is free to exploit the natural resources in it. This is related to existing conditions which indicate the existence of interdependence between government, private sector and communities being involved in the utilization of shared resources. The behavior of the parties related to the utilization of the Watershed greatly affects the condition of the existing Watershed Areas; where the performance of sub management of Cisadane Upstream watershed has not provided maximum results because the management is still going on sectorally.Keywords: Local Institution; Watershed Managemen; sub management of Cisadane Upstream watershedPengelolaan DAS menjadi aspek penting dalam menunjang pelestarian kawasan sekitarnya. Fungsi daerah hulu sebagai daerah tangkapan air harus dijaga dengan menjaga agar pemanfaatan kawasan agar terhindar dari daya dukung yang melebihi lingkungan. Peran masyarakat di daerah sekitarnya menjadi upaya penting untuk menjaga kelangsungan fungsi DAS. Penelitian ini bertujuan untuk menganalisis potensi dukungan kelembagaan lokal dalam pengelolaan DAS. Metode penelitian adalah studi kasus dimana data dikumpulkan melalui wawancara mendalam, diskusi kelompok terarah dan observasi partisipan. Analisis data dilakukan dengan menggunakan metode pendekatan kerangka kerja Situasi - Struktur - perilaku - kinerja. Hasil penelitian menunjukkan bahwa pemanfaatan SDA DAS dianggap sebagai sumber akses terbuka gratis dimana setiap orang bebas mengeksploitasi sumber daya alam di dalamnya. Hal ini terkait dengan kondisi yang ada yang menunjukkan adanya saling ketergantungan antara pemerintah, sektor swasta dan masyarakat yang terlibat dalam pemanfaatan sumber daya bersama. Perilaku para pihak terkait pemanfaatan DAS sangat mempengaruhi kondisi DAS yang ada; Dimana kinerja pengelolaan sub DAS Cisadane hulu belum memberikan hasil yang maksimal karena pengelolaannya masih berlangsung secara sektoral.Kata kunci: Kelembagaan Lokal; Pengelolaan Daerah Aliran Sungai; Sub DAS Ciaten Cisadane Hulu.